Medication and Substance Use among Pregnant Women in A Nigerian North Central Community, Kwara State, Nigeria - Olakunle, Jamiu Muslim; Abdulganiyu, Giwa; Fatima, Abdulazeez Iyabode; Onozare, Aliyu Fullaila (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The use of non-prescription medication and substances among pregnant women has become a global public health problem because of their tendency to cause untoward effects on the unborn child. This study was aimed at assessing medication and substance use among pregnant women and determines the knowledge of adverse effects associated with their use. A survey type of study involving 200 pregnant women in Erin-Ile community of Kwara State Nigeria. A semi structured questionnaire was used to elicit responses for the subjects. Data obtained were entered into SPSS v16 software for analysis. Descriptive data were presented in text, tables and chart forms and Chi square and logistic regression ware used to determine the significant level of association between categorical variables. P-value less than 0.05 were considered significant. The average age of respondents was 33.1±6.55. Thirty percent earned salary as government or private employee, 6.5% unemployed with the rest as artisans or traders. Ninety one percent (91%) claimed they always registered for antenatal but only 33% of them register at first three months of pregnancy. Financial constraint was the leading cause of delay in antenatal registration and 17% were ignorant of proper time to register. The most common ailment experienced in pregnancy was pain (80%) and up to 80% used medications that could have adverse effects on pregnancy. Ninety one percent of them engaged in the use of herbal preparations. Thirteen percent (13%) were aware of possible harmful effects of some substances taken during pregnancy. There was significant relationship between level of education and choice of antenatal method p=0.001 but this was not affected by the respondents occupational status, p=0.118. Most of the pregnant women were involved in taking medication and substances that could affect the health of unborn baby at one time of the pregnancy or the other. Method of antenatal use and time of commencement of antenatal were influenced by level of education of the women.